DHEA supplementation increases epithelial thickness, plain muscle tissue, and adult vaginal blood vessels (rattus norvegicus) after bilateral post-ovarectomy - Lis Widodo Peni; Wimpie Pangkahila (Fakultas Kedokteran Universitas Udayana, 2018)
Introduction: Seventy-five percent of menopausal women have menopausal syndrome, one of which is vaginal atrophy. DHEA is the only source of postmenopausal sex steroid hormones that provides estrogen and androgens according to cell needs to function normally. The aim of this study is to prove that DHEA supplementation orally can increase epithelium thickness, smooth muscle tissue, and the number of vaginal blood vessels of adult white mice (Rattus norvegicus) after bilateral ovarectomy. Method: This study used true experimental post-test only control group design using 36 white mice aged 10-12 weeks with a body weight of 180-200 grams after bilateral ovarectomy. The mice were divided into two groups with 18 mice each. The first group (controls) was given glycerin orally at a dose of 1 ml per day while the second group (treatment) was given 7.2 mg DHEA dissolved in 1 ml glycerin orally per day. On day 43, vaginal tissue was taken and histopathological examination was performed. Result: The results showed that the mean of epithelial thickness of treatment group was significantly higher than control group (51.397 µm vs. 29.755 µm; p: < 0.05). The smooth muscle thickness was also significantly higher in treatment group compared to control (74.136 µm vs. 47.428 µm; p: <0.05). Finally, the number of blood vessels was also significantly higher in treatment group (18.39 vs. 9.50; p:<0.05). Conclusion: It can be concluded that DHEA supplementation increases epithelium thickness, smooth muscle tissue thickness, and the number of vaginal blood vessels in adult rats after bilateral ovarectomy.